Tingkat Kecemasan berhubungan dengan Sikap dalam Pemberian Vaksin Covid-19 pada Anak Usia 6-11 Tahun - Robiatul Adawiyah; I Gusti Ayu Mirah; Adhi Ayik Second Ridho; Nurhayati (LPPM STIKES Mataram, 2024)
Introduction: COVID-19 is an infectious disease caused by a new type of coronavirus. To break the chain of transmission, vaccination should be carried. What the public is concerned about is the safety and efficacy of vaccines; side effects of vaccines; misunderstanding of the vaccination need; lack of trust in the health care system; and also the public’s lack of knowledge that the COVID-19 disease can be prevented by vaccination. Purpose: The purpose of this study was to determine the correlation between anxiety levels and reponse to administering the COVID-19 vaccine to children aged 611 years at SDN 1 Surabaya Utara, East Lombok in 2022. Design: The population were 80 students aged 6-11 years at SDN 1 North Surabaya, East Lombok. The sample consisted of 67 people, those who had not received the vaccine and those who had received the first dose of vaccine. The sampling technique used was cluster sampling. This study used a cross-sectional design. Data was collected using a questionnaire and analyzed using chi-square. Result: The results of this research showed that the sample was 67 respondents, the highest general data results were obtained with respondents aged 10 years as many as 23 respondents, (34.3%), aged 11 years as many as 23 respondents (34.3%). Meanwhile, the dominant female gender was 38 respondents (56.7%). The level of mild anxiety was 46 respondents (67.7%) and the highest attitude was negative, 35 respondents (52.2%). The results of the chi-square test showed a p value of 0.001<0.005. Conclussion: there was a correlation between the level of anxiety and the response to administering the COVID19 vaccine to students aged 6-11 years